Pengaruh Dukungan Manajemen, Tingkat Pengetahuan dan Keterlibatan Karyawan Terhadap Kinerja UMKM Binaan BSN - Tri Setyo Utomo, Anang; Annuridya Rosyidta Pratiwi Octasylva; Edward Sahat Tampubolon; Afina Putri Vindiana (Forum Kerjasama Pendidikan Tinggi, 2024)
A more expanding economy and an improvement in the general economic status of the nation are both outcomes that are brought about by the expansion of micro, small, and medium-sized businesses (MSMEs). It is important for micro, small, and medium-sized businesses (MSMEs) to implement measures that will reduce the chance of failure and bankruptcy in light of the current economic circumstances. Support from management, the quantity of knowledge available, and the level of participation from the workforce are the primary elements that influence success. For the purpose of this study, structural equation modeling (SEM) analysis was performed on a sample of 135 respondents who are participants in the Micro, Small, and Medium Enterprises (MSME) program that is supported by BSN. According to the findings, the provision of management assistance has a significant influence on the performance of micro, small, and medium-sized businesses (MSMEs). Furthermore, the study of the immediate effects has shown that the level of employee involvement has a direct impact on the performance of micro, small, and medium companies (MSMEs). MSMEs, on the other hand, do not have their performance affected by the degree of skill they possess. As a consequence, this discovery has a significant influence on the development of managerial support and employee participation, which ultimately leads to improved performance in micro, small, and medium-sized enterprises (MSMEs).The author's research fills a gap in the work that has been done before.